Implantation of perennial megathermic species in a natural grassland of the dune of San Luis, Argentina - Privitello, Liliana; Orive, J.; Rosa, S. T. (Cuban Journal of Agricultural Science, 2010)
In order to assess the effect of the sustainable management technology and the aggressive actions on the production system of natural psammophilous grassland, the accumulation of dry matter (DM) in a natural psammophilous grassland (degraded) was compared with that of the implanted megathermic species. Besides, the plants per surface area were evaluated, as well as the development of megathermic species, introduced at the end of the first growth cycle. According to the status, seven treatments were analyzed: natural grassland without changes (NG), subject to burning (B), to burning and tillage (BT), or implanted with weeping love grass (Eragrostis curvula) (WLG), with common finger grass (Digitaria eriantha) (CFG), with Makarikari grass (Panicum coloratum) (MG), or with mixture of megathermic species (M). A completely randomized design was applied. Parametric (ANOVA and DLS) and non-parametric (Kruskal-Wallis) analyses were applied. NG, B and BT had higher production of DM (15 g DM m-2 as average) (P > 0.05), and WLG, higher production and plant height (166.33 g of DM m-2 and 55 cm, P < 0.05). CFG manifested low density of plants (1.67 m-2), but higher efficiency of implantation (1.35 %), given the lower number of viable seeds sown (123 m-2). For the sowing density and the quality of the seed used, the highest number of plants grown in WLG (8.42 m-2, P < 0.05) put this species in an advantageous position in respect to the others. It is recommended to prevent the burning or the burning and tillage of the natural degraded grassland and replace it with perennial megathermic grasses such as the weeping love grass. Key words: megathermic forage plants, grasslands on sandy soil, burning, soil tillage.